How Risk Perception aand Financial Literacy Effect Overconfidence Bias and Investment Decisions Relationship - Mirfaqoh, Vella; Muktiyanto, Ali; Geraldina, Ira; Yusriani, Sri (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine the influence of overconfidence bias on investment decisions, which is mediated by risk perception and moderated by financial literacy. This research is quantitative research using causality analysis. The research instrument is a questionnaire with a likert scale of one to five points. The research used a random sampling technique with 400 capital market investors in Indonesia. Data were analyzed by SmartPLS4 software using the SEM PLS method. The research results show that overconfidence bias and risk perception positively affect investment decisions. Risk perception can positively and significantly mediate the relationship between overconfidence bias and investment decisions. Other results prove that financial literacy cannot moderate the relationship between overconfidence bias and investment decisions. This research implies that investors are expected to make investment decisions rationally and avoid detrimental investments.